2010
DOI: 10.1177/1077546309106521
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Global Stability of Beam-based Electrostatic Microactuators

Abstract: We investigate the dynamics and global stability of a beam-based electrostatic microactuator, which is modeled as a first-order approximation of a reduced-order model (ROM) derived using the differential quadrature method (DQM). We show that the ROM dynamics is qualitatively similar to that of a higher-order approximation. We simulate the occurrence of dynamic pull-in for excitations near the first primary resonance using the finite difference method (FDM) and long-time integration. Limit-cycle solutions are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 25 publications
0
37
0
Order By: Relevance
“…They showed that dynamic pull-in occurs under voltages lower than the static pull-in voltage, as low as 25%, when the frequency of the AC component is in the neighborhood of a resonant frequency. On the other hand, Najar et al [21] and Lenci and Rega [22] studied the basin of attraction of bounded motions and showed that the erosion of the basin of attraction is the principle reason for the occurrence of dynamic pull-in by homoclinic bifurcation. They showed that smoothness of the boundary of the basin of attraction of bounded motions can be lost and replaced with fractal tongues as the excitation amplitude is increased.…”
Section: Introductionmentioning
confidence: 98%
“…They showed that dynamic pull-in occurs under voltages lower than the static pull-in voltage, as low as 25%, when the frequency of the AC component is in the neighborhood of a resonant frequency. On the other hand, Najar et al [21] and Lenci and Rega [22] studied the basin of attraction of bounded motions and showed that the erosion of the basin of attraction is the principle reason for the occurrence of dynamic pull-in by homoclinic bifurcation. They showed that smoothness of the boundary of the basin of attraction of bounded motions can be lost and replaced with fractal tongues as the excitation amplitude is increased.…”
Section: Introductionmentioning
confidence: 98%
“…Only the branch of period-two orbits, subsequent to the first period-doubling bifurcation, is shown due to the small span of the higherorder orbits. A homoclinic bifurcation was reported by Najar et al [17] to interrupt an incomplete cascade of period-doubling bifurcations and to result in dynamic pull-in of an open-loop electrostatic resonator. In our case, the presence of the close-loop controller allows the cascade of period-doubling bifurcation to continue culminating in chaos due to a homoclinic entanglement.…”
Section: System Response Atmentioning
confidence: 94%
“…In fact, the electrostatic force grows and approaches infinity as the resonator displacement grows and approaches the size of the capacitor gap d → g. On the other hand, the beam stiffness k is finite, which causes the static equilibrium of the resonator to lose stability at about one-third of the gap g in a phenomenon known as static pull-in. The static and dynamic response of uncontrolled electrostatic MEMS resonators have been studied extensively by many researchers, for example Najar et al in [17,23].…”
Section: The Close-loop Electrostatic Resonatormentioning
confidence: 99%
See 1 more Smart Citation
“…In the last few years, scientific researchers have been focusing on nanotechnology and the resulting nano-materials which play key roles in many engineering devices at the nano-scale used in several applications including microactuators, microswtiches, biosensors, nanowires, nanoprobes, ultra-thin films and micro-and nano-electromechanical systems (MEMS and NEMS) studied in works of (Hung and Senturia, 1999;Li et al, 2003;Moser and Gijs, 2007;Pei et al, 2004;Najar et al, 2010). In fact, nano-materials have special mechanical, chemical, electrical, optical and electronic properties.…”
Section: Introductionmentioning
confidence: 99%